2018
DOI: 10.1007/s10443-018-9694-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characterization of Carbon Fiber-Reinforced Carbon Composites

Abstract: Carbon fiber-reinforced carbon (C/C) composites consist in a carbon matrix holding carbon or graphite fibers together, whose physical properties are determined not only by those of their individual components, but also by the layer buildup and the material preparation and processing. The complex structure of C/C composites along with the fiber orientation provide an effective means for tailoring their mechanical, electrical, and thermal properties. In this work, we use the Laser Flash Technique to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 80 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…However, these scattering processes are predominantly dominant at different temperature ranges. Using a calorimetric method, we found that values on thermal diffusivity and thermal conductivity measured in-plane to the fiber axis decreased with respect to those obtained out-plane of laminate [24,25]. There is not a significant difference in thermal diffusivity values in warp and weft directions because the fiber counts in the warp and weft directions are equivalent without any porosity in either direction.…”
Section: Thermal Conductivity Of the Carbon Fiber Reinforced Geopolym...mentioning
confidence: 66%
See 1 more Smart Citation
“…However, these scattering processes are predominantly dominant at different temperature ranges. Using a calorimetric method, we found that values on thermal diffusivity and thermal conductivity measured in-plane to the fiber axis decreased with respect to those obtained out-plane of laminate [24,25]. There is not a significant difference in thermal diffusivity values in warp and weft directions because the fiber counts in the warp and weft directions are equivalent without any porosity in either direction.…”
Section: Thermal Conductivity Of the Carbon Fiber Reinforced Geopolym...mentioning
confidence: 66%
“…However, these scattering processes are predominantly dominant at different temperature ranges. Using a calorimetric method, we found that values on thermal diffusivity and thermal conductivity measured in-plane to the fiber axis decreased with respect to those obtained out-plane of laminate [24,25].…”
Section: Thermal Conductivity Of the Carbon Fiber Reinforced Geopolym...mentioning
confidence: 67%
“…ε of the electrothermal film (4 cm × 4 cm) was 66.7% at 10 V, which is higher than that of traditional electrothermal materials. , When the input voltage increases continuously, the heat response speed of the electrothermal film remains stable. Figure a describes the functional relationship between the operating temperature and the power density of the electrothermal film.…”
Section: Resultsmentioning
confidence: 90%
“…The studied material from technical textiles with a mass density of 60 kg.m À3 consisted of several layers combined by felting. 55,56 Due to the fact that the examined material consists of synthetic combustible materials, it can be classified in the fire reaction class E according to the test protocol according to EN 13501-1+A1. 57 To achieve the required fire safety, the products are modified with chemical substances that prevent not only flare-ups or ignition but also the spread of flames at various stages of the burning process.…”
Section: Materials and Flame Retardantsmentioning
confidence: 99%